2016
DOI: 10.4155/fso.15.88
|View full text |Cite
|
Sign up to set email alerts
|

Differences in T-cell infiltrates and survival between HPV+ and HPV- oropharyngeal squamous cell carcinoma

Abstract: Recent studies have suggested that immune cells as part of tumor's microenvironment could partly explain the better outcome in HPV-associated oropharyngeal carcinoma. We performed a systematic review of the literature focused on differences in immune-infiltrate in HPV+ versus HPV- oropharyngeal cancers. This comprehensive search yielded 4308 original papers, of which 20 satisfied our eligibility criteria. Increase in both circulating and tumor infiltrating CD8+ lymphocytes is mainly seen in HPV+ oropharyngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 19 publications
2
37
0
Order By: Relevance
“…In OPSCC tumors, HPV status is one of the key prognostic variable for survival; however, new and stronger predictors of survival might be identified exploring the interaction between immune cells and tumor cells in the tumor microenvironment. Previous studies investigated the role of the microenvironment in head and neck tumors with contradictory results . Here, we obtained a comprehensive “immune signature” of HPV‐negative and HPV‐positive OPSCCs and we found new potential prognostic markers for survival of OPSCC patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In OPSCC tumors, HPV status is one of the key prognostic variable for survival; however, new and stronger predictors of survival might be identified exploring the interaction between immune cells and tumor cells in the tumor microenvironment. Previous studies investigated the role of the microenvironment in head and neck tumors with contradictory results . Here, we obtained a comprehensive “immune signature” of HPV‐negative and HPV‐positive OPSCCs and we found new potential prognostic markers for survival of OPSCC patients.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies investigated the role of the microenvironment in head and neck tumors with contradictory results. 10 Here, we obtained a comprehensive "immune signature" of HPV-negative and HPVpositive OPSCCs and we found new potential prognostic markers for survival of OPSCC patients. More specifically, expression of HLA-DP/DQ/DR on tumor cells, the numbers of CD68+ CD163+ TAMs in the tumor-associated stroma, and the numbers of CD8+ FoxP+ cells in the tumor were established in our multivariate analyses as independent prognostic markers of survival in oropharyngeal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have reported a higher number of TILs, in particular CD8 + T cells within tumor and stroma, in HPV + tumors compared with HPV − tumors [229233]. Increased numbers of FOXP3 + T regs , PD-1 + T cells and CD20 + B cells within immune infiltrates in HPV + tumors have also been described [234,235].…”
Section: Tils In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…Interestingly, a B cell signature distinguished HPV + from HPV − tumors, suggesting B cells rather than T cells account for the increased TILs seen in HPV + tumors [236]. Immunohistochemical studies have shown CD8 + and FOXP3 + TILs to significantly correlate with improved prognosis in oropharyngeal HPV + tumors [229236] and probably also HPV − tumors [233,236]. …”
Section: Tils In Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…According to several studies, a more prominent immune response is observed in HPV-positive tumors compared to HPV-negative tumors, and some studies suggested that TILs play a more important role in HPVpositive tumors than in HPV-negative tumors [15,48,57,58], which might explain the lack of prognostic value of T-cell markers in our patient cohort. However, there are also studies that suggest the opposite [14,59].…”
mentioning
confidence: 99%